Effects of Electrical Stimulation of Olivocochlear Fibers in Cochlear Potentials in the Chinchilla - Elgueda, Diego (Springer-Verlag, 2011)
The mammalian cochlea has two types of sensory cells; inner hair cells, which receive auditory-nerve afferent innervation, and outer hair cells, innervated by efferent axons of the medial olivocochlear (MOC) system. The role of the MOC system in hearing is still controversial. Recently, by recording cochlear potentials in behaving chinchillas, we suggested that one of the possible functions of the efferent system is to reduce cochlear sensitivity during attention to other sensory modalities (Delano et al. in J Neurosci 27:4146–4153, 2007). However, in spite of these compelling results, the physiological effects of electrical MOC activation on cochlear potentials have not been described in detail in chinchillas. The main objective of the present work was to describe these efferent effects in the chinchilla, comparing them with those in other species and in behavioral experiments. We activated the MOC efferent axons in chinchillas with sectioned middle-ear muscles by applying current pulses at the fourth-ventricle floor. Auditory-nerve compound action potentials (CAP) and cochlear microphonics (CM) were acquired in response to clicks and tones of several frequencies, using a round-window electrode. Electrical efferent stimulation produced CAP amplitude suppressions reaching up to 11 dB. They were higher for low to moderate sound levels. Additionally, CM amplitude increments were found, the largest (≤ 2.5 dB) for low intensity tones. CAP suppression was present at all stimulus frequencies, but was greatest for 2 kHz. CM increments were highest for low-frequency tones, and almost absent at high frequencies. We conclude that the effect obtained in chinchilla is similar to but smaller than that observed in cats, and that the effects seen in awake chinchillas, albeit different in magnitude, are consistent with the activation of efferent fibers.